IMPLEMENTASI METODE MARR-HILDERTH OPERATOR UNTUK MENDETEKSI TEPI CITRA IKONOS - Zalukhu, Yusman; Sunandar, Hery; Hondro, Rivalri Kristianto (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Ikonos imagery is a satellite image that has high spatial resolution with an accuracy of one meter pixels for panchromatic and four meters to multispektral. Ikonos imagery is often used to map the process, view, measure and memoniotring areas of work/activities on the Earth. Ikonos image of Government also often use it for things like national security evaluation against the occurrence of the disaster, city planning, mineral exploration and mine planning monitoring of agriculture, and others. Image digital imaging results over long distances using satellite is often there are disturbances in the form of light distortion, noise or other distractions that cause the object on the image less obvious or obscure. This discussion on the research being done is knowing the process of detection on image by calculating the difference between two dots are bertetanggan, and is in the process of smoothing and thresholding on image ikonos. The methods used in this research is a method of Marr-Hilderth. In addition, a process that is done on this research is conducting a testing method against Marr-Hilderth, which can be implemented to fix the blurry objects on images ikonos. The results of this research is to generate image ikonos with display clear object with the menerapakan method of the Marr-Hilderth and tested using the matlab application version 7.8 (r2009a).Keywords: Ikonos image, image processing, method of Marr-Hilderth, Matlab 7.8